Organic carbon accumulation in modern sediments of the Angola basin influenced by the Congo deep-sea fan. (August 2017) - Baudin, François; Martinez, Philippe; Dennielou, Bernard; Charlier, Karine; Marsset, Tania; Droz, Laurence; Rabouille, Christophe
Abstract: Geochemical data (total organic carbon-TOC content, δ 13 Corg, C:N, Rock-Eval analyses) were obtained on 150 core tops from the Angola basin, with a special focus on the Congo deep-sea fan. Combined with the previously published data, the resulting dataset (322 stations) shows a good spatial and bathymetric representativeness. TOC content and δ 13 Corg maps of the Angola basin were generated using this enhanced dataset. The main difference in our map with previously published ones is the high terrestrial organic matter content observed downslope along the active turbidite channel of the Congo deep-sea fan till the distal lobe complex near 5000 m of water-depth. Interpretation of downslope trends in TOC content and organic matter composition indicates that lateral particle transport by turbidity currents is the primary mechanism controlling supply and burial of organic matter in the bathypelagic depths.